2004
DOI: 10.1242/jcs.01159
|View full text |Cite
|
Sign up to set email alerts
|

Sequential myofibrillar breakdown accompanies mitotic division of mammalian cardiomyocytes

Abstract: The contractile tissue of the heart is composed of individual cardiomyocytes. During mammalian embryonic development, heart growth is achieved by cell division while at the same time the heart is already exerting its essential pumping activity. There is still some debate whether the proliferative activity is carried out by a less differentiated, stem cell-like type of cardiomyocytes or whether embryonic cardiomyocytes are able to perform both of these completely different dynamic tasks, contraction and cell di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
123
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 144 publications
(137 citation statements)
references
References 63 publications
10
123
1
Order By: Relevance
“…2, 4). Our observations are consistent with Ahuja et al (2004), demonstrating that myofibrils need to be disassembled during proliferation.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…2, 4). Our observations are consistent with Ahuja et al (2004), demonstrating that myofibrils need to be disassembled during proliferation.…”
Section: Resultssupporting
confidence: 90%
“…Nonessential amino acids are not often reported as required additive for the culture of cardiomyocyte cells (Burt 1982;Sreejit et al 2008). Though Sreejit et al (2008) and Song et al (2000) report using 1% gelatin and Ahuja et al (2004) reported using fibronectin as a pre-coat for myocyte culture dishes, such pre-coat steps are not often reported (Burt 1982;Nuss and Marban 1994;Fu et al 2005;Rosenblatt-Velin et al 2005;Nickson et al 2007). We, however, determined that a pre-coating with laminin was absolutely necessary for effective embryonic myocyte adhesion.…”
Section: Resultsmentioning
confidence: 99%
“…Even with the addition of pre-plating steps to reduce the population of cardiac fibroblasts and endothelial cells, the remaining fibroblasts will undergo cell proliferation and significantly change the cultured cell-population over time. 23,32,33 . Usage of AraC should be judged , such as phenylephrine (0.1 mM, preferentially for neonatal rat cardiomyocytes; Sigma P6126), or isoproterenol (1 μM, preferentially for neonatal mouse cardiomyocytes; Sigma I6501) greatly increases sarcomerogenesis, spreading of cardiomyocytes on the plate as well as spontaneous beating of cells.…”
Section: Proliferation Inhibitorsmentioning
confidence: 99%
“…During embryonic development, cardiomyocytes undergo cycles of myofibril assembly and disassembly that accompany each round of cell division [43]. During mitosis, Z-disks and actin filaments appear to disassemble before myosin filaments and myomesin ( figure 10, step 7).…”
Section: Myofibril Disassembly Pathwaysmentioning
confidence: 99%